Root Cause Analysis In Ensuring Patients Safety: A Narrative Review - Malaika Irshad; Saleema Begum (Journal of the Pakistan Medical Association, 2026)
Patient safety, as defined by World Health Organisation is “the absence of preventable harm to a patient during the process of healthcare”. It is imperative to understand common surgical errors in order to implement measures for improving safety and, consequently, the outcomes of surgery. The current narrative comprised a comprehensive literature search on PubMed, Cochrane, Scopus and Google Scholar databases, focussing on surgical safety protocols, root-cause analysis and complementary methodologies, pre-procedure verifications, structured checklists, failure modes and effects analyses, incident reporting systems and multidisciplinary team reviews of adverse outcomes, to highlight the role of root-cause analysis in enhancing patient safety in surgical specialties. Root-cause analysis, when combined with sound safety practices, forms the foundation of surgical error prevention and patient safety. A system-based approach, along with effective teamwork and communication, is essential for sustainable improvements in healthcare quality and patient care. Keywords: Patient safety, Root cause analysis, Surgical errors.